Evaluation of the self-eye examination method for health promotion - Maria Alzete de Lima; Jennara Candido do Nascimento; Abel Brasil Ramos da Silva; Lívia Moreira Barros; Lorita Marlena Freitag Pagliuca; Joselany Áfio Caetano (SciELO, 2018)
ABSTRACT Objective To evaluate the self-eye examination practice as a tool to promote the ocular self-evaluation. Method Quasi-experimental study developed in a university of Piauí with sample of 324 students between January and May 2014. A team of thirteen researchers made observations during the self-examination followed by an ocular screening. Results There was no agreement on the hypothesis of defense that the ocular exam could help to observe the eyes health, p-value>0.3. However, the exam was considered as easy to accomplish (99.7%) and that not only the physician can perform the eye exam (99.4%). The awareness about eye care is identified as the main purpose of this booklet (97.6%), (χ2= 186.01; p=0.001). The results highlight the booklet can be used in the teaching process of self-eye examination (84.6%). Although the defense that its fulfilment can replace the consultation with the ophthalmologist (23.8%%) cannot be accepted (χ2= 46.34), the self-exam must be done routinely (82.4%). Conclusion The results prove that the learning through virtual booklet is possible and supports self-care with the eyes by performing the self-exam.